What happens to intolerant, relapsed or refractory chronic myeloid leukemia patients without access to clinical trials? - Guilherme Rasia Bosi; Laura Maria Fogliatto; Tito Emilio Vanelli Costa; Kamila Castro Grokoski; Mariana Pinto Pereira; Nathan Bugs; Marco Kalil; Christina Fraga; Liane Esteves Daudt; Lucia Mariano da Rocha Silla (Hematology, Transfusion and Cell Therapy, 2019)
Objective: To assess clinical outcomes of intolerant, relapsed or refractory patients who could not be treated with new tyrosine kinase inhibitors or experimental therapies. Methods: A retrospective cohort of 90 chronic myeloid leukemia patients in all phases of the disease treated with imatinib mesylate as their first TKI therapy, and with dasatinib or nilotinib as the next line of therapy. We evaluated clinical outcomes of these patients, with special focus on the group that needed more than two therapy lines. Results: Thirty-nine percent of patients were refractory or intolerant to imatinib. An 8-year overall survival rate of the patients who went through three or more lines of treatment was significantly lower, compared to those who were able to maintain imatinib as their first-line therapy (83% and 22%, respectively p < 0.01). Decreased overall survival was associated with advanced-phase disease (p < 0.01), failure to achieve major molecular response in first-line treatment (p < 0.01) and interruption of first-line treatment due to any reason (p = 0.023). Failure in achieving complete cytogenetic response and major molecular response and treatment interruption were associated with the progression to the third-line treatment. Conclusion: The critical outcome observed in relapsed, intolerant or refractory chronic phase CML patients reflects the unmet need for this group of patients without an alternative therapy, such as new drugs or experimental therapies in clinical trials. Broader access to newer treatment possibilities is a crucial asset to improve survival among CML patients, especially those refractory or intolerant to first-line therapies. Keywords: Chronic myeloid leukemia, Imatinib mesylate, Dasatinib, Nilotinib, Survival analysis